THE RELATIONSHIP BETWEEN LANGUAGE LEARNING STRATEGIES AND VOCATIONAL LEARNERS’ EFL PROFICIENCY - Yustitiasari, Hilda _ (Lingual Journal of Language and Culture; Vol 8 No 2 (2019): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2019.v08.i02.p07, 2020)
Abstract Language learning strategies (LLS) are perceived as tools for teacher to educate the learners behave self-directed learning. It also known, improving language proficient. In the case of vocational college students, they practically use self-directed learning in learning English outside classroom since they should pass the TOEFL test after the internship as the requirement of graduation. Hereby, this study identifies: (1) the frequently language learning strategy used by vocational college learners, (2) the relationship between language learning strategy and English proficiency, (3) the strategy used by learners which could predict learners proficient. The participant is 52 students of Politeknik Kota Malang in 2016- 2017 academic year which done the TOEFL test and willing to complete the Strategy Inventory of Language Learning (SILL). This study employed quantitative approach and correlational research as the research design to identify the relationship between variables. There are six strategies of language learning strategies by Oxford (1990) as the independent variables (predictors) and English proficiency (criterion) as the dependent variable. Therefore, multiple regression analysis employed in this study. The result showed that metacognitive strategy reported highly used by learners. While compensation, cognitive, social strategies reported medium used by learners. The low strategy used was affective and memory strategies. Although, language learning strategy cannot simultaneously predict the English proficiency there is one strategy that can be used to predict English proficiency, namely compensation strategy. Keywords: Language Learning Strategies, EFL Learners, English Proficiency.